Implementation of the gs1 global traceability standard by market operators for the production of flour confectionery products used use of car ob powder - Bozhko, Anastasiia; Usatyuk, Svitlana (My University, 2022)
The GS1 Global Traceability Standard has been found to include: identification of participants and trading partners, trade items and events; marking and/or methods of labeling and/or affixing labels on goods; identification of types and types of data to be collected and stored; determination of methods and minimum requirements for keeping records and archival documents, in particular for their storage. The sequence of development of the traceability system for the market operator for the production of flour confectionery products using carob powder is proposed. The requirements for applying the Global Trade Item Number (GTIN) to finished products are analyzed, which guarantees the assignment of a unique control number to each product.

Встановлено, що глобальний стандарт простежуваності GS1 включає: ідентифікацію учасників і торгових партнерів, предметів торгівлі та подій; маркування та/або способи маркування та/або наклеювання ярликів на товари; визначення типів і видів даних, які збираються та зберігаються; визначення способів і мінімальних вимог до ведення діловодства та архівних документів, зокрема до їх зберігання. Запропоновано послідовність розробки системи простежуваності для оператора ринку з виробництва борошняних кондитерських виробів з використанням порошку ріжкового дерева. Проаналізовано вимоги до застосування глобального номера торгової одиниці (GTIN) до готової продукції, що гарантує присвоєння кожному продукту унікального контрольного номера.
Keywords: Global Traceability Standard (GS1); Глобальний стандарт простежуваності (GS1); traceability system; система відстеження; flour confectionery; борошняні кондитерські вироби; carob powder; порошок ріжкового дерева; Global Trade Item Number (GTIN); Глобальний номер одиниці торгівлі (GTIN); кафедра експертизи харчових продуктів